How Age, Cognitive Function and Gender Affect Bimanual Force Control - Rudisch, Julian; Müller, Katrin; Kutz, Dieter F.; Brich, Louisa; Sleimen-Malkoun, Rita; Voelcker-Rehage, Claudia (Frontiers in Physiology, 2020)
Coordinated bimanual control depends on information processing in different intra- and interhemispheric networks that differ with respect to task symmetry and laterality of execution. Aging and age-related cognitive impairments but also sex can have detrimental effects on connectivity of these networks. We therefore expect effects of age, cognitive function and sex on bimanual force coordination. We furthermore expect these effects to depend on the characteristics of the task (i.e., difficulty and symmetry). 162 right handed participants (19 younger adults [YA], 21-30 years, 9 females; 52 cognitively healthy older adults [HOA], 80-91 years, 32 females; and 91 older adults with mild cognitive impairments [MCI] 80-91 years, 37 females) performed isometric bimanual force control tasks that required following constant or alternating (cyclic sine-wave) targets and varied in symmetry, i.e., i) constant symmetric, ii and iii) asymmetric (with constant left and alternating right or vice versa), iv) alternating in- and v) alternating antiphase (both hands alternating with 0° or 180° relative phase respectively). We analysed general performance (time on target), bimanual coordination as coupling between hands (linear correlation coefficient) and structure of variability (i.e., complexity measured through detrended fluctuation analysis). Performance and coupling strongly depended on task symmetry and executing hand, with better performance in symmetric tasks and in asymmetric tasks when the left hand produced a constant and the right hand an alternating force. HOA and MCI, compared to YA, showed poorer performance (time on target) and reduced coupling in in- and antiphase tasks. Furthermore, both groups of OA displayed less complex structure in alternating force production tasks, a marker of reduced control. In addition, we found strong sex effects with females displaying reduced coupling during in- and antiphase coordination and less complex variably structure in constant force production. Results of this study revealed strong effects of age, but also sex on bimanual force control. Effects depended strongly on task symmetry and executing hand, possibly due do different requirements in interhemispheric information processing. So far, we did not find a clear relationship between behavioural markers of bimanual force control and age-related cognitive decline (compared to healthy aging), making further investigation necessary.